Espectroscopia vibracional em cristais do ácido trans-cinâmico complexado com európio sob condições extremas - Pereira, Jose Enedilton Medeiros (2014)
This work is focused on characterization of a polycrystalline sample of the coordination compound with ions Eu3+ using as a binder the trans-cinnamic acid , [Eu(cin)3]. The interest in coordination with lanthanide compounds is due to their large technological applications. The process of luminescence of coordination compounds containing lanthanide, also called antenna effect, has a main objective the use of new ligands with various applications, both in increasing the efficiency of energy receptors in the ultraviolet region and the development of biomarkers. In this work, to characterize the polycrystalline material, Raman spectroscopy was used to determine the vibrational behavior of the material at ambient temperature and pressure. It was also shown the behavior of the compound at low temperatures, in which variations in various vibrational modes were observed, indicating thus the occurrence of phase transition. Using a diamond anvil cell the material was studied by high hydrostatic pressure Raman spectroscopy. The purpose of this methodology was to map possible phase transitions and discover the occurrence of possible polymorphism. However, until the pressure reached in the experiments - about 5.2 GPa - it was found that the original phase remained stable. A discussion of the luminescence of the sample is also provided in this work.